Hermilio Valdizán and history of Peruvian medicine - Lastres, Juan B. (1935)
The communication from some flashes of that medicine that took figures such as Ramon Lull and the nascent Servetus was slow and progressive Cologne. You could say that seize both Spanish and indigenous, of incipient progress of each culture; but no such each medicine, its practice often primitive, marched disunited and the Indian element is typecast in their negativity, unable sufficiently benefit the few Spanish doctors arsenal of indigenous plantras, many of them highly recommended medical properties .